Gestational weight gain and its association with obstetric and fetal outcome - Rajesh, Samhita; Rajakumar, Shery A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Gestational weight gain (GWG) is a key determinant of maternal and neonatal outcomes, influenced by maternal pre-pregnancy body mass index (BMI), nutrition, and adherence to guidelines. Deviations from optimal GWG, particularly inadequate weight gain, are associated with adverse outcomes, including preterm birth, low birth weight (LBW), and increased caesarean delivery rates. While Institute of Medicine (IOM) guidelines offer recommendations for appropriate GWG, adherence remains suboptimal in many populations, particularly in developing countries. Methods: A retrospective observational study was conducted at Chettinad Hospital and Research Institute, involving 264 postnatal mothers. Participants were categorized into two groups based on GWG relative to IOM guidelines: group 1 (inadequate GWG) and group 2 (adequate GWG). Data on maternal height, pre-pregnancy weight, first- and third-trimester weight, and outcomes were retrieved from antenatal records. Statistical analyses were performed to evaluate associations, with significance set at p<0.05. Results: Inadequate GWG was observed in 50% of participants. Group 1 had higher rates of caesarean delivery (52.3% versus 32.6%, p=0.02), preterm births (21.9% versus 9.1%, p=0.01) and LBW neonates (28.8% versus 9.1%, p<0.001) compared to group 2. Mean birth weight was significantly lower in group 1 (2.7±0.4 kg versus 3.2±0.3 kg, p<0.001). Conclusions: Inadequate GWG is significantly associated with adverse maternal and neonatal outcomes, including increased caesarean delivery rates, preterm births, and LBW. Pre-pregnancy BMI is a critical determinant of GWG adequacy. These findings underscore the need for tailored antenatal interventions to promote optimal GWG and improve pregnancy outcomes.